THE EXCELLENCE OF EXTENSIVE AND INTENSIVE READING - Missriani Missriani (Universitas PGRI Palembang, 2015)
Abstract Extensive reading is reading in large numbers so that the reader can understand the material being read as well as a whole. Extensive Reading done with the following steps: a) survey the title page, preface, table of contents, and index; b) setting skim through the pages of text quickly. To find the main idea of the text pages or; c) glancing each page of text just to find a particular word or information desired. Intensive reading can be done in the manner of reading short texts with guidance and in a relaxed situation. The purpose of intensive reading is to help students acquire the detailed meaning of the text, to develop the skills of reading, such as identifying main ideas and recognizing text connectors and to increase vocabulary and grammar knowledge is as follows. 1) improving language learning in areas such as spelling, vocabulary, grammar, and structure of the text; 2) improving knowledge skills; 3) improving reading and writing skills; 4) greater enjoyment of reading; 5) a more positive attitude towards reading; 6) a higher likelihood of developing the habit of reading. Keywords: extensive, intensive, reading